Inactivation of the left auditory cortex impairs temporal discrimination in the rat - Rybalko, Natalia; Suta, Daniel; Popelár, Jirí; Syka, Josef (Behavioural brain research, 2010)
The left auditory cortex (AC) in humans is involved in the processing of the temporal parameters of acoustical signals, specifically in speech perception, whereas the right AC plays the dominant role in pitch and melody perception. The hemispheric lateralization of acoustical signal processing in non-human mammals is less explored. The present study examined the ability of rats to detect or discriminate a series of gaps in continuous noise under conditions of unilateral or bilateral reversible inactivation of the AC. The results showed that muscimol-induced reversible inactivation of the left AC suppresses the ability of rats to discriminate between acoustical stimuli of different temporal parameters (duration or repetition rate), whereas inactivation of the right AC results in no change or only a mild decrease in discrimination ability. Hemispheric asymmetry was observed only in the case of gap discrimination tasks, but not in a gap detection task. Our findings demonstrate that, similarly as in humans, the left AC in the rat plays the dominant role in temporal discrimination. These data provide further evidence for the functional asymmetry of the mammalian brain, which appears in a relatively early phase of evolution.
Keywords: muscimol; Auditory Diseases, Central; Auditory Perceptual Disorders; GABA Agonists; Rats; klasické podmiňování; Auditory Cortex; funkční lateralita; Disease Models, Animal; Discrimination, Psychological; Functional Laterality; poruchy sluchové percepce; krysa rodu Rattus; centrální poruchy sluchu; modely nemocí na zvířatech; ženské pohlaví; zvířata; Acoustic Stimulation; Muscimol; elektrický šok; GABA agonisté; Electroshock; akustická stimulace; diskriminace (psychologie); Female; Conditioning, Classical; sluchové korové centrum; Animals